Exploring the influence of culture in curriculum transformation using the Mmogo Method™ - Nthabiseng Ann Molise; Yvonne Botma; Deirdre VanJaarsveldt (International Journal of Africa Nursing Sciences, 2022)
Transitioning education from a teacher-centred approach to student-centred learning through a transformative competency-based curriculum remains a challenge to many disciplines. An added consideration during such a transition is the interconnection between culture and curriculum. One such example in the nursing and widwifery discipline took place in the transformation of the curriculum in Lesotho in 2014. However, this link between culture and curriculum was not taken into consideration. Difficulty in parting with didactic lecturing resulted in curriculum drift in all except one nursing education institution, where the educators are mostly from other African countries. Literature highlights culture as a factor that could negatively influence curriculum transformation, which gave rise to the question: How does culture influence the implementation of curriculum transformation? A qualitative descriptive interpretative design was adopted, and data were collected by means of the Mmogo-Method™. This culture-sensitive projective technique was conducted in four phases - creation of context, construction, discussion, and debriefing. Seven purposively selected midwifery educators, from three different institutions, participated and the session was video recorded. Through a thematic data analysis of transcriptions and images, three main categories were identified: cultural conventions, the midwifery and nursing professions, and midwifery education. The sub-categories of each were influenced by social interactions. Emic interpretation revealed power to control as an emergent theme. Social interactions are a common thread in patriarchy and student-centred learning. However patriarchy as a factor of power to control is contrary to the underpinnings of student-centred learning, thus negatively influencing curriculum transformation. Insights into cultural influences could guide engagement of the educators in knowledge-construction towards culturally congruent, quality education to ultimately improve midwifery practice for positive health outcomes.